Microenvironment, tumor cell plasticity, and cancer. Issue 1 (January 2015) - Faurobert, Eva; Bouin, Anne-Pascale; Albiges-Rizo, Corinne
<x xml:space="preserve">Abstract</x> Purpose of review Much effort has been devoted to determining how cellular and noncellular components of the tumoral niche initiate and promote cancer development. Cancer cells perceive biochemical signals from components of the extracellular matrix (ECM) and sense physical features, such as matrix stiffness and cell confinement. The past decade has seen a better understanding of the biophysics and mechanobiology associated with cancer cells. Indeed, loss of mechanisms controlling the production, the degradation, and the remodeling of ECM contributes to tumor growth or cell dissemination by affecting cell contractility in response to ECM stiffness and by stimulating mechanical dependence of growth factor activation. Results Cell plasticity allows adaptative strategies for cancer cells to survive or eventually escape from tumoral environment through modification of the microenvironment–cell interface, internal tension increase, and nuclear deformation partly leading to intratumoral heterogeneity. However, although alteration of the biomechanical properties of the ECM are sufficient to promote cell migration and invasion in cancer cells, this microenvironment can also provide a hospitable niche for tumor dormancy and resistance to cancer therapy. Conclusion The review will focus on how physicochemical properties of ECM might promote tumor growth or cell dissemination or on the contrary maintain quiescent state of cancer cells. It is crucial to clarify the molecular basis of mechanotransduction in the development and progression of tumors to identify new potential biomarkers and anticancer therapeutic targets.